PERBEDAAN KEBOCORAN MIKRO SEMEN IONOMER KACA MODIFIKASI RESIN KONVENSIONAL DAN SEMEN IONOMER KACA MODIFIKASI RESIN NANO SEBAGAI BAHAN RESTORASI PADA GIGI DESIDUI (EKSPERIMENTAL LABORATORIS) - , NATALIA, DR. drg. Indah Titien Soeprihati, SU., Sp.KGA(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A kind of restoration adhesive failure is a gap between the restoration and the tooth structure, known as microleakage. Microleakage is influenced by particle size of restoration. Aim of this study is to compare the microleakage of conventional resin modified glass ionomer cement and nano resin modified glass ionomer cement in restorating deciduous teeth. Laboratory experiment was performed in 20 post extracted incisive deciduous teeth. The cavity was made by round bur, diameter 2,5mm. All of the teeth got separated into 2 groups. Group 1, 10 teeth were restorated with conventional resin modified glass ionomer cement and group 2, 10 teeth were restorated with nano resin modified glass ionomer cement. All teeth were then subjected to thermocycling. Each of tooth was covered with nail polish and the apices of all of the teeth were sealed with sticky wax. All of the teeth were immersed in blue dye and then they were sectioned labiopalatally. The specimen were then studied under stereomicroscope with a magnification 60x. Measurement of the depth of the blue dye infiltration was analyzed by independent sample T-test. It was known that there were significant correlation between microleakage of the teeth that were restorated with conventional resin modified glass ionomer cement and the teeth that were restorated with nano resin modified glass ionomer cement. Conclusion, conventional resin modified glass ionomer cement showed lower microleakage than nano resin modified glass ionomer cement in restorating deciduous teeth. Key words: microleakage, conventional resin modified glass ionomer cement, nano resin modified glass ionomer cement